2007
DOI: 10.2337/dc06-2043
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Healing of Neuropathic Ulcers of the Foot in Diabetes and Its Relationship to Ulcer Duration and Ulcer Area

Abstract: OBJECTIVE -To examine the outcome of neuropathic foot ulcers and to seek associations between healing and features of the ulcers at baseline.RESEARCH DESIGN AND METHODS -Data were collected prospectively during the course of routine management. All patients were selected who presented to a single unit between 1 January 2000 and 31 December 2004 with neuropathic foot ulcers and without evidence of either peripheral arterial disease or infection. Associations were sought between ulcer characteristics at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
77
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 16 publications
12
77
2
1
Order By: Relevance
“…Given the relatively poor chance of healing in patients with a toe pressure <30 mmHg or a TcPO 2 <25 mmHg, we suggest considering imaging and revascularisation in these patients. Urgent imaging and treatment should also be considered in patients with PAD and higher pressure levels, in the presence of other predictors of poor prognosis, including infection or large ulcer surface area [24]. Finally, in light of their limited diagnostic and prognostic utility, none of the tests described earlier can completely rule out PAD as a cause of impaired wound healing in a foot ulcer that does not respond to optimal treatment.…”
Section: Rationalementioning
confidence: 99%
“…Given the relatively poor chance of healing in patients with a toe pressure <30 mmHg or a TcPO 2 <25 mmHg, we suggest considering imaging and revascularisation in these patients. Urgent imaging and treatment should also be considered in patients with PAD and higher pressure levels, in the presence of other predictors of poor prognosis, including infection or large ulcer surface area [24]. Finally, in light of their limited diagnostic and prognostic utility, none of the tests described earlier can completely rule out PAD as a cause of impaired wound healing in a foot ulcer that does not respond to optimal treatment.…”
Section: Rationalementioning
confidence: 99%
“…Even if it was eventually shown that, despite the odds, an augmented programme had no effect on the incidence of new ulceration, it can be assumed that the programme would include the simple instruction that all new disease should be referred promptly for expert assessment and that it should be explained to the patient how they can ensure this happens. There are data to show that while an education programme may not reduce the incidence of ulceration, it may lead to a decreased incidence of amputation [10], and it is known that early expert assessment is associated with improved clinical outcome [11,12].…”
mentioning
confidence: 99%
“…EB guidelines recommend referral to specialized care as part of a multidisciplinary provider team to achieve optimal outcomes for ulcers extending 4-12 weeks [10][11][12][13] . A correlation between ulcer duration at the time of first specialty evaluation and the time to subsequent healing was established by two studies 14,15 , suggesting that timely referral to specialty care could be an important part of good ulcer care.…”
Section: Introductionmentioning
confidence: 99%